Diseño de alternativas de mejora al manejo de residuos sólidos urbanos generados en la parroquia urbana Celica, provincia de Loja - Quezada Ramírez, Juan Pablo (2024)
The problem of waste management in the Celica urban parish is related to the generation of waste and its inadequate management. To address this problem, the main objective of the research was to design alternatives aimed at improving the management of solid waste generated in the Celica parish. In order to achieve this purpose, it began with the characterization of the solid waste generated in homes, shopping centers, educational centers, agricultural centers, veterinary clinics and hospitals in the Celica urban parish. This characterization was carried out using statistical sampling methods proposed by the Pan American Center for Sanitary Engineering and Environmental Sciences (CEPIS). To do this, a total of 150 samples were collected over 8 consecutive days, which allowed us to obtain data on per capita generation (GPC), total daily generation (GTD) and the physical composition of solid waste. The results revealed that the urban parish Celica has a generation of 5,085 Ton/day, with the most significant GPC being that of the household stratum with 0.60 kg/inhabitant/day. Regarding the average physical composition of solid waste, it is estimated that 69.43% is organic, 25.57% inorganic waste and 5% sanitary waste. In the second instance, the current diagnosis of the current management of solid waste was carried out using the Zero Waste methodology established by the sections of Zaman. Allowing the identification of problems at various stages of management through interviews, perception surveys and checklists. These include the lack of separation of waste at source, inefficiency in sweeping and cleaning public areas, the lack of training of collection operators and the absence of adequate infrastructure for the use, treatment and final disposal of solid waste. Finally, improvement alternatives were proposed for the management of solid waste in the Celica urban parish, based on the SWOT Matrix, the Cause and Effect Diagram, and the Objective Tree. These proposals covered nonformal environmental education programs, waste separation and storage initiatives, sweeping plans for public spaces and training for collection operators, as well as a program for the use of organic solid waste.